Family support and anxiety levels in chronic kidney disease patients undergoing hemodialysis - Edison, Shandi Setiawan; Andoko, Andoko; Keswara, Umi Romayati (JOURNAL OF Mental Health Concerns, 2026)
Background: The incidence of chronic kidney disease (CKD) in Indonesia is 0.38% of the total population of 252.124.458, approximately 713.783 individuals. In Lampung Province, it is estimated that there are 25,842 CKD patients in 2023, ranking Lampung 18th in Indonesia for this disease. Purpose: To determine the relationship between family support and anxiety levels in chronic kidney disease patients undergoing hemodialysis at RSUD Abdul Moeloek, Lampung Province, in 2025. Method: A quantitative analytical design with a cross-sectional approach. The population consists of 150 hemodialysis patients at RSUD Abdoel Moloek in Lampung Province, with a sample size of 110 respondents. The sampling technique used is purposive sampling. Data analysis is conducted using the chi-square statistical test Results: Based on frequency distribution, 36.4% of respondents reported low family support, while 63.6% reported good family support. A p-value of 0.001 was obtained, with an odds ratio of 4.026. Conclusion: There is a relationship between family support and anxiety levels (p value 0.001, OR 4.02) in chronic kidney failure patients undergoing hemodialysis at RSUD Abdul Moeloek, Lampung Province, in 2025. Healthcare providers need to implement programs involving families to enhance emotional support for chronic kidney failure patients, such as educational videos and posters about supporting hemodialysis patients Keywords: Anxiety; Family Support; Hemodialysis.